Motivation Theories and Destructiveness Phenomenon - Gyulambaryan, Nona (ՀՀ ԳԱԱ)
The topical issue for this scientific research is the problem of human motivation in modern society. Various social sciences provide extensive material for studying the problem of motivation. In different historical periods, society treated the expressions of human motivation differently. According to the forms of the organization of society, various theories of motivation were presented, which found their application in psychological science, sociology, cultural studies, and anthropology. Along with the problem of studying motivation, there is a growing interest among theorists and practitioners in the phenomenon of destructiveness. In psychological science, there is a need to compare and analyze these phenomena. An interdisciplinary study of theories of motivation and the phenomenon of destructiveness revealed certain ties between destructive behavior of a person and his motivations. In particular, the article considered the psychological category of motivational frustration, which means the impossibility of achieving goals and the inadequate expression of motivations. Актуальной темой для данного научного исследования является проблема мотивации человека в современном обществе. Различные социальные науки предоставляют обширный материал для изучения проблемы мотивации. В различные исторические периоды времени общество по-разному относилось к проявлениям мотивации человека. Соответственно особенностям организации общества, формировались различные теории мотивации, которые нашли свое применение в психологической науке, социологии, культурологии и антропологии. Наряду с проблемой изучения мотивации наблюдается растущий интерес среди теоретиков и практиков к феномену деструктивности. В психологической науке возникает необходимость сопоставления и анализа этих феноменов. Այս գիտական հետազոտության արդիական թեման է ժամանակակից հասարակության մեջ անձի մոտիվացիայի խնդիրը: Հասարակական տարբեր գիտակարգերը բազմաբնույթ նյութեր են ներկայացնում մոտիվացիայի խնդիրը ուսումնասիրելու համար։ Պատմական տարբեր ժամանակաշրջաններում հասարակությունը տարբեր վերաբերմունք է ունեցել մարդկային մոտիվացիայի դրսևորումների նկատմամբ։ Ըստ հասարակության կազմակերպման առանձնահատկությունների՝ ձևավորվել են մոտիվացիայի տարբեր տեսություններ, որոնք իրենց կիրառությունն են գտել հոգեբանության, սոցիոլոգիայի, մշակութաբանության և մարդաբանության մեջ։
Keywords: Social and Humanitarian Sciences